Reactive control of zoom while fixating using perspective and affine cameras. - Tordoff, B; Murray, D (2004)
This paper describes reactive visual methods of controlling the zoom setting of the lens of an active camera while fixating upon an object. The first method assumes a perspective projection and adjusts zoom to preserve the ratio of focal length to scene depth. The active camera is constrained to rotate, permitting self-calibration from the image motion of points on the static background. A planar structure from motion algorithm is used to recover the depth of the foreground. The foreground-background segmentation exploits the properties of the two different interimage homographies which are observed. The fixation point is updated by transfer via the observed planar structure. The planar method is shown to work on real imagery, but results from simulated data suggest that its extension to general 3D structure is problematical under realistic viewing and noise regimes. The second method assumes an affine projection. It requires no self-calibration and the zooming camera may move generally. Fixation is again updated using transfer, but now via the affine structure recovered by factorization. Analysis of the projection matrices allows the relative scale of the affine bases in different views to be found in a number of ways and, hence, controlled to unity. The various ways are compared and the best used on real imagery captured from an active camera fitted with a controllable zoom lens in both look-move and continuous operation.